1987
DOI: 10.1902/jop.1987.58.6.393
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Lipopolysaccharide on Individual Root Surfaces at Varying Times Following in Vivo Root Planing

Abstract: Material with endotoxin activity has been detected in extracts prepared from pooled, periodontally involved teeth, and it has been shown that root planing in vivo reduces the level of such material. However, questions concerning the concentration of endotoxin on the diseased surfaces of individual teeth and questions concerning how rapidly individual root planed tooth surfaces retoxify in vivo have not been addressed previously. Citric acid extracts were prepared from individual, periodontally diseased teeth t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28][29][30] In vitro studies on the reduction of the biological activities of LPS with mild alkali, sodium dodecylsulphate, and EDTA (ethylene diamine tetraacetic acid) had been previously carried out. [31][32][33] In this study, Er: YAG laser irradiation has been found to be effective for dental hard tissues with little damage to the surrounding structures, except the irradiated areas.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30] In vitro studies on the reduction of the biological activities of LPS with mild alkali, sodium dodecylsulphate, and EDTA (ethylene diamine tetraacetic acid) had been previously carried out. [31][32][33] In this study, Er: YAG laser irradiation has been found to be effective for dental hard tissues with little damage to the surrounding structures, except the irradiated areas.…”
Section: Discussionmentioning
confidence: 99%
“…The innate host response is critical to maintaining a clinically healthy periodontium (18,61), and studies have shown that in healthy individuals a highly orchestrated protective response is found (18,61). P. gingivalis, which resides in close proximity to the gingival epithelial cell surface, releases copious amounts of outer membrane vesicles containing LPS (23,24) which can penetrate periodontal tissue (37,39,53) and have direct inhibitory effects on the highly vascularized tissue adjacent to the tooth root surface. The interruption of endothelial cell responses to LPS is similar to earlier observations (15,35) demonstrating inhibition of IL-8 secretion after invasion of epithelial cells by viable P. gingivalis.…”
Section: Fig 4 Inhibition Of P38 Map Kinase Phosphorylation By P Gmentioning
confidence: 99%
“…This bacterium releases copious amounts of outer membrane vesicles containing LPS (19,20), which can penetrate periodontal tissue (38,39,50) and thus participate in the destructive innate host response associated with disease. The potential contribution of P. gingivalis LPS to the disease process is not clear, however, due to complex innate host responses to this cell wall component (4).…”
mentioning
confidence: 99%